Lymphedema distichiasis syndrome may be caused by FOXC2 promoter‐enhancer dissociation and disruption of a topological associated domain. Issue 1 (27th October 2020) - Wallis, Mathew; Pope‐Couston, Rachel; Mansour, Julia; Amor, David J.; Tang, Paisu; Stock‐Myer, Sharyn
Abstract: Lymphedema distichiasis syndrome (LDS) is a rare autosomal dominant condition characterized by lower limb lymphedema, distichiasis, and variable additional features. LDS is usually caused by heterozygous sequence variants in the FOXC2 gene located at 16q24, but in one previous instance LDS has resulted from a balanced reciprocal translocation with a breakpoint at 16q24, 120 kb distal to the FOXC2 gene suggesting a position effect. Here, we describe a second family with LDS caused by a translocation involving 16q24. The family were ascertained after detection of a paternally inherited balanced reciprocal translocation t(16;22)(q24;q13.1) in a pregnancy complicated by severe fetal hydrops. There was a past history of multiple miscarriages in the father's family, and a personal and family history of lymphedema and distichiasis, consistent with the diagnosis of LDS. Using whole genome amplified DNA from single sperm of the male proband, bead array analysis demonstrated that the FOXC2 gene was intact and the chromosome 16 breakpoint mapped to the same region 120Kb distal to the FOXC2 gene. This case highlights the clinical consequences that can arise from a translocation of genomic material without dosage imbalance, and that it is increasingly feasible to predict and characterize possible effects with improved access to molecular techniques.